2011
DOI: 10.5935/1678-9741.20110052
|View full text |Cite
|
Sign up to set email alerts
|

Perfusato autólogo retrógrado no circuito de circulação extracorpórea em pacientes adultos

Abstract: Introduction: Retrograde autologous priming (RAP) is a cardiopulmonary bypass (CPB) method, at low cost. Previous studies have shown that this method reduces hemodilution and blood transfusions needs through increased intraoperative hematocrit.Objective: To evaluate RAP method, in relation to standard CPB (crystalloid priming), in adult patients.Methods: Sixty-two patients were randomly allocated to two groups: 1) Group RAP (n = 27) of patients operated using the RAP and; 2) Control group of patients operated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…At the same time, priming of conventional crystal solution in CPB will inevitably cause serious hemodilution and reduction of plasma colloid osmotic pressure, which will produce adverse effects ( 1 - 4 ). It has been demonstrated that the applications of retrograde autologous priming (RAP) in adult rheumatic heart disease and cardiac surgeries for coronary heart diseases can improve the hematocrit (Hct) level, reduce postoperative chest drainage volume and allogeneic blood transfusion, indicating that RAP is a safe and cost-effective blood conservation technique ( 5 - 8 ). The application of RAP in pediatric CPB can reduce priming volume, and keep a high Hct level during trans-instrument process ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, priming of conventional crystal solution in CPB will inevitably cause serious hemodilution and reduction of plasma colloid osmotic pressure, which will produce adverse effects ( 1 - 4 ). It has been demonstrated that the applications of retrograde autologous priming (RAP) in adult rheumatic heart disease and cardiac surgeries for coronary heart diseases can improve the hematocrit (Hct) level, reduce postoperative chest drainage volume and allogeneic blood transfusion, indicating that RAP is a safe and cost-effective blood conservation technique ( 5 - 8 ). The application of RAP in pediatric CPB can reduce priming volume, and keep a high Hct level during trans-instrument process ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three studies, 25 , 26 , 27 of which one randomized trial, did not find any significant difference in PRBC transfusions between the RAP and conventional CPB group. Moreover, the three studies that found no effect of RAP all use higher priming volumes in both the RAP and control groups compared to the studies that found a significant benefit of RAP.…”
Section: Individual Studiesmentioning
confidence: 90%
“…When taking a closer look at these three studies, it becomes apparent that the study by Reges et al 25 is a prospective but small-scale pilot study. The small sample size (n = 27 in the RAP group) may be the reason the authors could not identify a significant difference between the RAP and non-RAP group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Sao Paulo, Brazil showed that RAP increases hematocrit during surgery, especially in people with anemia, followed by decreased hemolytic reactions due to decreased blood transfusion. However, some results reported the RAP as a useful method while some others not [10]. Kearsey et al study showed that there were no differences in blood transfusion, platelet, frozen plasma, 30-day mortality, reoperation, and the amount of hemoglobin between the RAP and the control group [11].…”
Section: Effect Of Retrograde Autologous Priming On Clinical Outcome Of Cardiopulmonary Bypassing On Patients Undergoing Coronary Artery mentioning
confidence: 99%